Celebrating the City: Pereira’s Centenary Amidst Fine Arts, Mass Culture, and Local Patriotism (1963) (2024)
This article examines the cultural and social activities that Pereira’s elites designed for the city’s centenary celebrations. Firstly, it analyses the cultural agenda that aimed to bring Pereirans and visitors closer to different expressions of national culture. Then, the text focuses on describing the popular events that took place in the city’s main public spaces. Thirdly, it addresses the place occupied by musical performances through which social distinctions were deepened according to the type of rhythms, audiences, and stages used. Finally, it studies the day of August 30, 1963, as a solemn event that served to express the political tensions between the city, the department, and the nation. Theoretically, the research is framed within the cultural and social history of commemorations, for which press information and official documentation from local archives were used to trace the organization, development, and meaning of the festivity. The development of the centenary evidenced the complementarity between an emerging popular culture, with a strong commercial sense, and the promotion of local patriotism, which characterized these events in a context of the accelerated modernization of the country.